2023
DOI: 10.1038/s41467-023-37954-3
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of human megakaryocyte-biased hematopoietic stem cells by biomimetic Microniche

Abstract: Limited numbers of available hematopoietic stem cells (HSCs) limit the widespread use of HSC-based therapies. Expansion systems for functional heterogenous HSCs remain to be optimized. Here, we present a convenient strategy for human HSC expansion based on a biomimetic Microniche. After demonstrating the expansion of HSC from different sources, we find that our Microniche-based system expands the therapeutically attractive megakaryocyte-biased HSC. We demonstrate scalable HSC expansion by applying this strateg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 57 publications
(78 reference statements)
0
2
0
Order By: Relevance
“…This, to some extent, also influences the bias of HSC lineage differentiation. In other words, HSCs situated in a specific ecological niche are only capable of receiving particular stimuli and then differentiate toward the lineage to which they are biased [ 22 , 23 ]. Moreover, a recent study revealed the origin of heterogeneity in zebrafish embryonic hematopoietic stem progenitor cells.…”
Section: Overview Of Hematopoiesis and Megakaryopoiesismentioning
confidence: 99%
“…This, to some extent, also influences the bias of HSC lineage differentiation. In other words, HSCs situated in a specific ecological niche are only capable of receiving particular stimuli and then differentiate toward the lineage to which they are biased [ 22 , 23 ]. Moreover, a recent study revealed the origin of heterogeneity in zebrafish embryonic hematopoietic stem progenitor cells.…”
Section: Overview Of Hematopoiesis and Megakaryopoiesismentioning
confidence: 99%
“…In this study, we investigated the effect of the combination of NAM and UM171 on HSC expansion ex vivo . In humans, CD34+CD38-cells are classic HSPCs, and HSCs can be functionally divided into ST-HSCs (CD34+CD38-CD45RA-CD49f+CD90-) and LT-HSCs (CD34+CD38-CD45RA-CD49f+CD90+) [ [14] , [15] , [16] , [17] , [18] , [19] , [20] ]. We found that NAM+UM171 exhibited superior activity in expanding phenotype defined LT-HSCs proportionally and quantitatively, the expansion folds of LT-HSCs reached 753.16 ± 83.02.…”
Section: Introductionmentioning
confidence: 99%